The Flower of Evil: On the Phenomenon of Boredom - Zagorac, Ivana (Array, 2014)
This paper focuses on the concept of boredom, which is often described as the product of modern times. However, the writings of Lucretius and Seneca warn of taedium vitae and horror loci, early Christian monks suffered under the demon of acedia, while the malady of melancholy plagued 17th and 18th century Europe. The Industrial Revolution altered the quality of human being in time, now represented by the image of a mechanical clock, and invented concepts of leisure and boredom. Modern time has worked hard on democratization of boredom. The relative freedom from the necessity, the growing reliance on consumer goods as a way of energizing ourselves, and the sense of liberation and emancipation felt by many, provide the conditions where boredom can so easily, and effortlessly, be experienced. The first part of the paper explores interpretative transformations of the phenomenon of boredom, followed by the analysis of existential disturbance that can be provoked by boredom. The conclusion deals with the question of whether boredom represents a threat that must be fought against using all means possible, or whether it can be seen as a motivating power to induce far-reaching change.